The Inflammatory Response After Ischemic Stroke: Targeting β2 and β1 Integrins - Edwards, Danielle N.; Bix, Gregory J. (Frontiers in Neuroscience, 2019)
Ischemic stroke is a leading cause of death and disability with limited therapeutic options. Resulting inflammatory mechanisms after reperfusion (removal of the thrombus) result in cytokine activation, calcium influx, and leukocytic infiltration to the area of ischemia. In particular, leukocytes migrate toward areas of inflammation by use of integrins, particularly integrins B1 and B2. Integrins have been shown to be necessary for leukocyte adhesion and migration, and thus are of immediate interest in many inflammatory diseases, including ischemic stroke. In this review, we identify the main integrins involved in leukocytic migration following stroke (aLb2, aDb2, a4b1, and a5b1) and targeted clinical therapeutic interventions.